Managerial Pattern and Work Relations at Traditional Pond in Pangkajene and the Island District (Milkfish Aquaculture Case in Bonto Manai Village) - Agusanty, Harnita; Kasri, Kasri; Khaeriyah, Andi; Arief, Andi Adri; Akbar, Akbar; Gosari, Beny Audy Jaya; Amir, Faisal; Hasani, M. Chasyim (Torani Journal of Fisheries and Marine Science, 2022)
Improving the quality of traditional farmers on a technical, social and economic scale, is strongly influenced and determined by the capacity to carry out pond business activities related to managerial patterns and work relationships that are formed.  This research was conducted in October – December 2021. Milkfish (Chanos-chanos) aquaculture business in Bonto Manai Village was chosen as the case, because the aquaculture system managed by the community is dominated the traditional aquaculture system. The purpose of this research is to analyze the knowledge of traditional aquaculture as a technical practice in managing aquaculture businesses, as well as to analyze the work relations of traditional aquaculture businesses which are internalized in the local culture of the community. The methodology used is a case research method with a descriptive qualitative data analysis approach described in the life history of the informants. The results showed that traditional farmers in milkfish (Chanos-chanos) aquaculture in Bonto Manai Village have acquired knowledge gained through experience passed down from generation to generation, starting from the construction and management of pond subgrade, seed stocking, rearing, harvest and post-harvest. Accompanied by rituals based on belief as a traditional value. The managerial pattern and work relations in the management of traditional pond business have three types of management, namely; aquaculture business which is self managed by the owner of the aquaculture land with involving two to three workers, aquaculture business which is managed based on a leasing system, and aquaculture business which is managed by a rapture system. Keywords: Managerial Pattern, Work Relations, Traditional Pond, Milkfish